Kepatuhan Perawat terhadap Pelaksanaan Metode SBAR pada Transfer Pasien untuk Meningkatkan Keselamatan Pasien di Rumah Sakit Murni Teguh Medan - Cici Yuyani; Seriga Banjarnahor (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: Patient safety in hospitals is a crucial aspect in efforts to prevent unwanted events (KTD) that can endanger patients. Unwanted events (KTD) often occur during the patient transfer process in hospitalized patients. Objective: To determine nurses' compliance with the implementation of the sbar method in patient transfers to improve patient safety. Method: This study is a quantitative study with a descriptive approach. The study was conducted in the inpatient ward of Murni Teguh Hospital Medan. The population, namely 252 implementing nurses and 50 samples were obtained. Sampling was carried out using purposive sampling. Analysis was carried out univariately in a frequency distribution table. Results: This study shows that the characteristics of nurses at Murni Teguh Hospital Medan are mostly female (92.0%), aged 20-35 years (52.0%), with a Bachelor's degree in Nursing (76.0%). Nurses' compliance in carrying out SBAR communication during patient transfers at Murni Teguh Hospital Medan is in the compliant category (60.0%), fairly compliant category (34.0%), and less compliant category (6.0%). Conclusion: Nurses are compliant in implementing the SBAR method during patient transfers to improve patient safety. Suggestion: Nurses at Murni Teguh Hospital Medan are advised to continue to improve their competence in using SBAR communication, especially in critical patient transfer situations.